"Credit Risk and Credit Rationing:" Comment - Ryder, Harl E. (Quarterly Journal of Economics, 1962)
Journal Article “Credit Risk and Credit Rationing:” Comment Get access Harl E. Ryder, Jr. Harl E. Ryder, Jr. University of Illinois Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 76, Issue 3, August 1962, Pages 471–479, https://doi.org/10.2307/1879633 Published: 01 August 1962